Comparative Study of Macerated and Soxhlet-Extracted Moringa Oleifera Leaf Extracts: LC-MS-Based Metabolomic Profiling, Antioxidant Activity, and In Silico Target Prediction - Muadifah, Afidatul; Sulastri, Sulastri; Sowe, Momodou Salieu; Lintang, Anggun; Warni, Tri (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2025)
Moringa leaves (Moringa oleifera L.) are rich in secondary metabolites such as flavonoids, alkaloids, tannins, saponins, and terpenoids, which function as natural antioxidants. This study aimed to analyze the metabolite profile of M. oleifera leaf extracts obtained through two extraction techniques using LC-MS, evaluate their antioxidant activity via the DPPH assay, and predict the interaction between NADPH oxidase (as a receptor) and key plant-derived compounds through molecular docking. LC-MS results indicated that the maceration method yielded 101 secondary metabolites, with flavonoid derivatives comprising 70.99% of the extract, dominated by five key compounds including Kaempferol 3-O-robinobioside and Luteolin-7-glucoside. In contrast, the Soxhlet method resulted in 83 identified compounds, with a higher proportion of flavonoids (75.61%), and prominent compounds including quercetin-3-O-glucoside and Kaempferol 3-(6G-malonylneohesperidoside). Antioxidant testing with DPPH at concentrations of 10, 50, and 100 ppm revealed the Soxhlet extract had a stronger activity (IC₅₀ = 14.328 ppm) compared to the macerated extract (IC₅₀ = 32.092 ppm), with statistically significant differences (p < 0.05). Molecular docking demonstrated that Kaempferol 3-(6G-malonylneohesperidoside) exhibited the strongest binding affinity to NADPH oxidase (-10.1 kcal/mol), followed by other flavonoid derivatives. These findings underscore the antioxidant potential of M. oleifera, particularly from Soxhlet extraction, and suggest its promising application in pharmaceutical development as a natural antioxidant source.